Rapid viral rebound after analytical treatment interruption in patients with very small HIV reservoir and minimal on‐going viral transcription. Issue 2 (27th February 2020) - Pannus, Pieter; Rutsaert, Sofie; De Wit, Stéphane; Allard, Sabine D; Vanham, Guido; Cole, Basiel; Nescoi, Coca; Aerts, Joeri; De Spiegelaere, Ward; Tsoumanis, Achilleas; Couttenye, Marie‐Madeleine; Herssens, Natacha; et al.
Abstract: Introduction: Viral remission after analytical treatment interruption (ATI), termed post‐treatment control, has been described in a small proportion of HIV‐positive patients. This phenomenon has been separately associated to both low levels of HIV‐1 proviral DNA as well as cell‐associated RNA. We investigated whether the combination of both parameters could help predict delayed viral rebound after treatment interruption (TI). Methods: We conducted an open single‐arm ATI study in four Belgian HIV reference centres from January 2016 to July 2018. Eligible participants were adults who had fewer than 50 HIV‐1 RNA copies/mL for more than two years, more than 500 CD4 cells/µL for more than three months, and were in general good health. Consenting participants who had fewer than 66 copies total HIV‐1 DNA (t‐DNA) and fewer than 10 copies cell‐associated HIV‐1 unspliced RNA (US‐RNA) per million peripheral blood mononuclear cells (PBMCs), interrupted therapy and were monitored closely. Antiretroviral therapy (ART) was resumed after two consecutive viral loads exceeding 1000 copies or one exceeding 10, 000 copies/mL. The primary outcome was the proportion of participants with fewer than 50 HIV‐1 RNA copies/mL 48 weeks after TI. Secondary outcomes were time to viral rebound, the frequency of serious adverse events (AEs) and evolution of t‐DNA and US‐RNA after TI. Results: All 16 consenting participants who interrupted therapy experienced rapid viral rebound two to eight weeks after TI. No serious AEs were observed. Levels of t‐DNA and US‐RNA increased after TI but returned to pre‐ATI levels after treatment restart. None of the studied demographic, clinical and biological parameters were predictive of time of viral rebound. Conclusions: The combination of low levels of t‐DNA and US‐RNA in PBMCs, corresponding respectively to a small and transcriptionally silent viral reservoir, is not predictive of viral remission after TI in patients on ART.